Religious Americans and Political Choices - Marie A. Failinger (International Institute of Islamic Thought, 2007)
The Journal of Law and Religion held its 2006 Law, Religion, and Ethics symposium, “Religious Americans and Political Choices,” at Hamline University. The event focused on reframing the divide between the so-called religious “Red State” and secular “Blue State” political discourses. Its objective was to discover what the major American faith traditions share by way of political values and understandings about the critical issues facing the United States, particularly in the areas of race, poverty, environmental protection, and restorative justice. Keynoter David Gushee (Graves Professor of Moral Philosophy, Union University) began with an “insider’s critique” of how evangelicals have allowed political conservatives to capture their commitments on issues that do not fully reflect their broad priorities as Christians. He argued that evangelical Christians should cast a wary eye on politico-religious alignments in accord with their basic principles. Evangelicals, Gushee noted, believe that God is redeeming the world on His own time and that a Christian’s first loyalty must be to Jesus Christ as Lord, not parties, and teaching the Good News as well as loving God and one’s neighbor. This evangelical commitment entails the recognition that political activity cannot redeem the world; but because the world is an arena of moral concern, politics is a necessary (if sinful) part of life. Thus, Christians must seek peace and prosperity for the entire human community, with a consistent ethic of life that embraces those members of the wider world community who have been marginalized. In the panel on race and poverty, David Skeel (professor of law, University of Pennsylvania), an evangelical Christian, continued this theme by discussing the important role that evangelicals and other Christians have played in pursuing debt relief for Africa, despite their traditional suspicion of big government. He called for religious Christians to identify the “moral blind spots of our age” and demand that political leaders recognize the equal worth of every human being, both at home and abroad ...